2013
DOI: 10.1063/1.4811830
|View full text |Cite
|
Sign up to set email alerts
|

Predicting longevity of submerged superhydrophobic surfaces with parallel grooves

Abstract: A mathematical framework is developed to predict the longevity of a submerged superhydrophobic surface made up of parallel grooves. Time-dependent integrodifferential equations predicting the instantaneous behavior of the air-water interface are derived by applying the balance of forces across the air-water interface, while accounting for the dissolution of the air in water over time. The calculations start by producing a differential equation for the initial steady-state shape and equilibrium position of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
75
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 43 publications
5
75
0
Order By: Relevance
“…The results also indicated that the theory of Poetes et al [11] was applicable for a much wider range of pressures. In a related theoretical study, Emami et al [110] modeled the longevity of parallel grooves superhydrophobic surfaces subjected to different pressures. It was found that for grooves with higher width-to-depth ratios, the critical pressure was higher due to stronger resistance to deflection of the air-water interface from the air trapped in such grooves.…”
Section: Longevity Of Superhydrophobic Coatingsmentioning
confidence: 99%
“…The results also indicated that the theory of Poetes et al [11] was applicable for a much wider range of pressures. In a related theoretical study, Emami et al [110] modeled the longevity of parallel grooves superhydrophobic surfaces subjected to different pressures. It was found that for grooves with higher width-to-depth ratios, the critical pressure was higher due to stronger resistance to deflection of the air-water interface from the air trapped in such grooves.…”
Section: Longevity Of Superhydrophobic Coatingsmentioning
confidence: 99%
“…The sidewall of the trench has nanometer-scale roughness, as it was replicated from the "scalloped" surface [25] on the DRIE silicon mold. Let us first analyze how the trapped air is depleted from a hydrophobic trench after being submerged based on previous works [15,26,27]. Consider a simple trench with width w, length l, and depth h, as defined in Fig.…”
mentioning
confidence: 99%
“…Importantly for our purpose instead, a sample with single trench would allow clear images of one air-water meniscus; in comparison, multiple menisci in multiple trenches would overlap and blur the images. The transparent sample with a Let us first analyze how the trapped air is depleted from a hydrophobic trench after being submerged based on previous works [15,26,27]. Consider a simple trench with width w, length l, and depth h, as defined in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The importance has been recognized only very recently, as the plastron loss became the main roadblock against testing SHPo surfaces in turbulent flows especially in large facilities. Samaha et al (2012a) have measured that the longevity of the plastron was shortened as the flow rate over the SHPo surface increased, and Emami et al (2013) have numerically investigated the unsteady behavior of the plastron interface by considering the diffusion of trapped air over time. They showed that the maximum hydrostatic pressure sustainable above the plastron decreases with increasing width of the water-air interface.…”
Section: Introductionmentioning
confidence: 99%